Machine-based based subtalar pronator and supinator strength training increases rearfoot stability in male runners - Hagen, M.; Lahner, M.; Lahner, N. (Journal of Biomechanics, 2025)
Excessive pronation and increased pronation velocity of the foot due to excessive Subtalar Joint (STJ) motion have been discussed as major intrinsic factors for the pathophysiology of overuse running injuries. A possible strategy to reduce these risk factors is the use of the supinator muscles acting eccentrically during the support phase of running. We hypothesised that STJ-specific strength training of the supinator and pronator muscles would be more effective in reducing rearfoot motion compared to traditional plantarflexor and dorsiflexor exercises.